INCREASING STUDENTS’ SPEAKING ABILITY THROUGH ROLE PLAY TECHNIQUE: Teaching, Speaking, Role Play. - Balak, Gloria; Muntuuntu, Meity; Rorimpandey, Rinny (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2022)
This study aimed at finding out whether the use of role play could improve the students’ speaking ability or not. The goal of this study was to see if students' speaking improved after using role play. The quantitative method was used to conduct this study. This study used a pre-experimental design with a single group pre-test and post-test. The subject of this research was second grade of SMP Anugrah Tondano which consisted of 10 students. The tests were in the form fill in test with dialogue. The result of this research showed that the mean scores in the post-test was higher (76) than those of pre-test (45). It was found that students' speaking ability was still low before using Role play technique; however, it was found that students' speaking ability improved after implementing Role play technique. It could be concluded that, the use of role play was effective to increase students’ speaking ability